Tribological and mechanical investigation of coir-silk reinforced polypropylene based matrix composites. Issue 1 (February 2021) - Vinay Kumar, D; Nanjundaswamy, C.; Sachit, T.S.; Mohan, N
Abstract: Silane treated natural fibers such as silk, coconut coir is reinforced into the polypropylene (PP) with a varying weight fraction of fibers and matrixes are developed in twin screw extruder at a constant temperature followed by the hot compression molding. Totally three different weight percentage of the polymer composites are developed. Such as silk fiber reinforced composites (S-PP), coir fiber reinforced composites (C-PP) and silk along with coir fiber reinforced composites (S-C-PP). The developed composites are then subjected to various tests. The water absorption capabilities of the all three composites are investigated. The composites are tending to abrasive wear test as per the ASTM standards. Design of experiments L-9 orthogonal array was introduced to identify the optimal wear condition of the composites developed. From the results it is observed that the tricholo vinyl silane chemical treatment to the coir and silk fibers enhances the tribo-mechanical properties of the fiber reinforced polymer composites. Also, the wear life of the composites was increased by 35% and water absorption capability increased by 42%. The scanning electron microscopy helped in identifying the impact of wear test over the surface of the composites at higher magnifications. The detailed surface morphology was executed in order to identify the behavior of the composites upon application of load.